Effectiveness of Learning Assessment through Feedback with Test Essays - Marzam Marzam; Ambiyar Ambiyar; Ishak Aziz (Fakultas Bahasa dan Seni UNP, 2021)
The use of strategic and well-planned feedback in the assessment process is key to promoting learning. This article evaluates the role of the two-stage test process in guiding and assisting the learning of students in the second year of teaching materials at sendratasik Education Program, FBS Padang State University. After being given oral and written feedback without grades from the first test, students were given the opportunity to write different tests, the second test, and each was asked to choose which one was assessed. Students are generally very positive about the assessment process, most participate voluntarily and fully, learn a lot differently for the second test, and there is evidence of meta-cognitive awareness and understanding. Nevertheless, some students have difficulty and frustration in assessing the quality of their work. Discussions focus on learning processes and issues, on the usefulness of feedback and on formative test assessment procedures.